FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PARTISIPASI ANGGOTA CU MUARE PESISIR SIANTAN - Hoiyimah, Hoiyimah; Yusra, Abdul Hamid A.; Komariyati, Komariyati - (Fakultas Pertanian Universitas Tanjungpura, 2018)
Participation of members in an organization is important in achieving success. This study aims to determine the factors associated with the participation of members Cu Muare Coastal Siantan. Methods in this study using quantitative methods .. Data analysis using Rank Spearman Correlation with the help of the program Statistics Program For Social Science (SPSS) version 16.0. The results of member participation with basic education show a strong relationship. the participation of members with motivation shows a strong relationship. the participation of members with cooperative services shows a very strong relationship